Dilemmas of research as an institutional practice and biographical experience (Praxis Educativa, 2021)
This article examines some dilemmas posed by the analysis of the academic field of research in the university system. In order to do so, we recur to the experience recorded in a biographical-narrative text done by a teacher-researcher. In this biographical record, the traces, marks and voices of devices that refer toperformative forces that shape contemporary ideas of the university and that seek to perform the subjectivities and identities of academics are noticed. The dilemmas, although they are posed in a subjective register, are analyzed as effects of meaning generated by the instituting action of Academic Capitalism, the Global Reform of Higher Education and the Culture of Auditing as concurrent processes that operate in the regulation of the field. academic-scientific since the establishment of neoliberal policies in the Argentine university system since the nineties and that still persist. In this reading key, the unique dilemmas of the researcher bring out a dispute of meaning of greater scope generated by the transition towards a universitymodel based on the logic and governance instruments of Academic Capitalism.
Keywords: academic capitalism; academic profession; academics identities; biographical experience; university policies; academic global reforms.